Glucose-6-phosphate dehydrogenase deficiency and reduced haemoglobin levels in African children with severe malaria - Nguetse, Christian N. (Malar J, 2016)
BACKGROUND: Extensive studies investigating the role of host genetic factors during malaria associate glucose-6-phosphate dehydrogenase deficiency with relative protection. G6PD deficiency had been reported to associate with anti-malarial drug induced with haemolytic anaemia. METHODS: A total of 301 Gabonese, Ghanaian, and Kenyan children aged 6–120 months with severe malaria recruited in a multicentre trial on artesunate were included in this sub-study. G6PD normal (type B), heterozygous (type A(+)) and deficient (type A(−)) genotypes were determined by direct sequencing of the common African mutations G202A and A376G. Furthermore, multivariate analyses were executed to associate possible contributions of G6PD deficiency with baseline haemoglobin levels, parasitaemia and with severe malarial anaemia. RESULTS: Two hundred and seventy-eight children (132 females and 146 males) were successfully genotyped for G6PD variants. The overall prevalence of G6PD deficiency was 13 % [36/278; 3 % (4/132) female homozygous and 22 % (32/146) male hemizygous], 14 % (40/278) children were female heterozygous while 73 % (202/278) were G6PD normal [67 % (88/132) females and 78 % (114/146) males] individuals. Multivariate regression revealed a significant association of moderately and severely deficient G6PD genotypes with haemoglobin levels according to the baseline data (p < 0.0001; G6PD heterozygous: p < 0.0001; G6PD deficient: p = 0.009), but not with severe malarial anaemia (p = 0.66). No association of G6PD genotypes with baseline parasitaemia. CONCLUSIONS: In this study, moderately (type A(+)) and severely (type A(−)) G6PD deficiency showed significant association with lower haemoglobin concentrations at baseline in African children with severe malaria without leading to severe malarial anaemia. In addition, there was no association of G6PD variant types with parasite densities on admission.